Livestock research for development in a complex, messy world: Reflections on a decade of work for ILRI - Seré Rabé, Carlos (International Livestock Research Institute, 2011)
On 9 and 10 November 2011, the ILRI Board of Trustees hosted a 2‐day ‘liveSTOCK Exchange’ to discuss and reflect on livestock research for development. During the workshop, Carlos Seré, former Director General of ILRI reflected on his tenure.